2014
DOI: 10.1093/pubmed/fdu098
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with visit-to-visit systolic blood pressure variability in the US adults

Abstract: Obesity is associated with visit-to-visit systolic blood pressure variability. Additional research is required to replicate the reported results in prospective studies and evaluate approaches to reduce blood pressure variability observed in clinical settings among obese persons to reduce its subsequent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
3
13
1
1
Order By: Relevance
“…The results of the recent study (14) similarly designed as our research, which included more participants (14988) beloning to general population showed the positive correlation between both total and central obesity with BPV. BPV was 6.89 mmHg across study visits.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The results of the recent study (14) similarly designed as our research, which included more participants (14988) beloning to general population showed the positive correlation between both total and central obesity with BPV. BPV was 6.89 mmHg across study visits.…”
Section: Discussionsupporting
confidence: 64%
“…According to recent results (14,24,25), we have found, that values of visit-to-visit SBPV were significantly lower in non-obese hypertensive patients compared to obese hypertensive patients (7.37±3.94 vs. 11.29±5.67, p<0.001). This is probably caused by the increase in sympathetic activity, insulin and vascular resistence, and the concentrations of proinflammatory cytokines, which leads to the increased heart pumping activity in hypertension accompanied with obesity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[15,[26][27][28][29] The two phenomena are associated with cardiovascular morbidity, such as ischemic heart disease, stroke, peripheral vascular diseases; and cardiovascular mortality. [12][13][14][15][16][17][18][19] Yet, to our knowledge, the relationship between HNBP and VVBPV has not been explored before in any representative sample.…”
Section: Discussionmentioning
confidence: 98%
“…[1] Third, VVBPV is significantly associated with several cardiovascular outcomes: ischemic heart disease, heart failure, stroke, peripheral vascular diseases and cardiovascular mortality. [12][13][14][15][16][17][18][19] Researchers reported a significant positive relationship between hypertension and VVBPV; [19] however, to our knowledge, investigators have never tested the relationship between HNBP and VVBPV in a representative sample before. Thus, we analyzed NHANES III data to explore the relationship between these two conditions.…”
Section: Introductionmentioning
confidence: 98%